Water motion and vegetation control the pH dynamics in seagrass‐dominated bays. (14th August 2019) - James, Rebecca K.; van Katwijk, Marieke M.; van Tussenbroek, Brigitta I.; van der Heide, Tjisse; Dijkstra, Henk A.; van Westen, René M.; Pietrzak, Julie D.; Candy, Adam S.; Klees, Roland; Riva, Riccardo E. M.; Slobbe, Cornelis D.; Katsman, Caroline A.; et al.
Abstract: Global oceanic pH is lowering, which is causing great concern for the natural functioning of marine ecosystems. Current pH predictions are based on open ocean models; however, coastal zones are dynamic systems with seawater pH fluctuating temporally and spatially. To understand how coastal ecosystems will respond in the future, we first need to quantify the extent that local processes influence the pH of coastal zones. With this study, we show that over a single diurnal cycle, the total pH can fluctuate up to 0.2 units in a shallow seagrass‐dominated bay, driven by the photosynthesis and respiration of the vegetation. However, these biologically controlled pH fluctuations vary significantly over small distances. Monitoring conducted at neighboring sites with contrasting hydrodynamic regimes highlights how water motion controls the extent that the local pH is altered by the metabolism of vegetation. The interactive effects of hydrodynamics and vegetation were further investigated with an in situ experiment, where the hydrodynamics were constrained and thus the local water residence time was increased, displaying the counteractive effect of hydrodynamics on the pH change caused by vegetation. With this research, we provide detailed in situ evidence of the spatial variation of pH within marine ecosystems, highlighting the need to include hydrodynamic conditions when assessing the pH‐effects of vegetation, and identifying potential high‐pH refuges in a future low pH ocean.